ANALISIS PENGENDALIAN KUALITAS DENGAN MENGGUNAKAN METODE LEAN SIX SIGMA DI PT. XYZ - Ahmad Fauzi; Moch Tutuk Safirin (UPN Veteran Jawa Timur, 2021)
XYZ is a company that produces Medical Devices. One of the products produced is 16x16 hydrophilic sterile gauze. One of the factors that affect the quality of a product is the presence of defects in the product and waste which results in a longer lead time for a product. The investigative stages used in this study are using tools: seven tools, Big Picture Mapping, Value Stream Analysis (VALSAT) and then analyzing the causes of defects using the Ishikawa diagram (fishbone chart) where the output of this study is a proposed improvement using the FMEA method ( Failure Mode Effect and Analysis) to eliminate defects and waste that occur. Based on the research results, it is known that the type of waste identified by the calculation of Value Stream Activity and obtained Value Added with a percentage of 84.4%, Non Value Added by 1.0% and Necessary Non Value Added by 14.5%. From the results of production output in December 2019 to November 2020 amounting to 2,650,200 boxes, the number of defects is 1,316 boxes with an average sigma level of 5.16, while in FMEA it is known that the largest defects are spots with an RPN value of 504 and a suggestion for improvement is to place Experienced operators who have gone through the recruitment and training stages on superior qualifications on one machine according to their skills who understand SOPs and operators are given good comfort in the production process. Keywords: Lean Six Sigma, Seven Waste, DMAIC, FMEA, kasa steril hidrofil 16x16.